(untitled) (Research, Society and Development, 2022)
The advance in the use of technology in contemporary society allows people to live with greater ease and comfort, whether at home, at work or in leisure time. In educational institutions, technology can be applied in order to facilitate the work of teachers, teaching methods and student learning, in addition, technology also contributes to safety in the institution’s environments. Therefore, this work aims to present a model of monitoring system for students/academics, teachers and employees in educational institutions, with the purpose of facilitating the work of teachers, guaranteeing the safety of all people who attend the environment, guaranteeing legal security , contribute to the appreciation of the educational institution, before society, that implements a system with these purposes and contribute to the development of students and academics who use the arduino to create small projects of great relevance.